2017
DOI: 10.1093/eurheartj/ehx106
|View full text |Cite
|
Sign up to set email alerts
|

CardioScape mapping the cardiovascular funding landscape in Europe

Abstract: CV-research funding varies strongly between different nations with the EU providing 37% of total available project funding and clear geographical gradients exist. Data allow in depth comparison of funding for different research areas and led to a number of recommendations by the consortium. CardioScape can support CV research by aiding researchers, funding agencies and policy makers in their strategic decisions thus improving research quality if CardioScape strategy and technology becomes the basis of a contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Web of Science data including 2014 references were available mid-2015, the cardiovascular publications dataset was complete in 2016 and algorithms for analysis including re-iterative expert review required another 18 months. A similar time lag is seen in other studies that rely on data mining and processing 9 . Congress abstracts could be considered as a source to identify emerging topics but have several limitations.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Web of Science data including 2014 references were available mid-2015, the cardiovascular publications dataset was complete in 2016 and algorithms for analysis including re-iterative expert review required another 18 months. A similar time lag is seen in other studies that rely on data mining and processing 9 . Congress abstracts could be considered as a source to identify emerging topics but have several limitations.…”
Section: Discussionmentioning
confidence: 54%
“…The authors assigned research project to topics, based on the abstract text, using a semi-automatic process that tested and trained the data to more quickly allocate abstracts to a topic than depending solely on expert review. They produced a detailed taxonomy or classification of cardiovascular research based on the list of topics of the European Society of Cardiology, creating a hierarchical list of over 600 topics 9 …”
Section: Introductionmentioning
confidence: 99%
“…The European Society of Cardiology initiated and coordinated ‘A Survey of the European cardiovascular research landscape and recommendations for future research strategy (CardioScape)’. 5 The survey was converted into an online database that now provides an extensive overview of research activities at national and European levels and the respective sources of financial funding. CardioScape shows that cardiovascular research funding varies widely between nations in the European Union.…”
Section: Trends In Cardiovascular Researchmentioning
confidence: 99%
“…For instance, in Bulgaria, Croatia, Estonia, and Lithuania, no funding ≥ €100 000 per project was made available by funding bodies between 2010 and 2012. 5 Participation in consortia with West European countries is an attractive approach for increasing the involvement of Eastern European countries in drawing grant support for research projects.…”
Section: Trends In Cardiovascular Researchmentioning
confidence: 99%
“…Targeted scientific research funding and coordination by research institutes have been identified as the strongest opportunities (Maresova et al 2015). While the distribution of public research funding on cardiovascular research is heterogeneous (Pries et al 2018), the effectiveness of public funding from national and supranational levels such as the European Union's Framework 7 and Horizon 2020 programs on knowledge output is unclear. Previous evidence, irrespective of the industry, demonstrates the effectiveness of innovatory efforts by measuring R&D investments, human capital, and intermediary scientific institutes on the knowledge output of patents (Moreno et al 2005, Marrocu et al 2013, Fritsch, Franke 2004.…”
Section: Introductionmentioning
confidence: 99%